Macronutrients for Plants Growth and Humans Health - Monib, Abdul Wahid; Alimyar, Obaidullah; Mohammad, Mohammad Usman; Akhundzada, Mohammad Shafi; Niazi, Parwiz (Journal for Research in Applied Sciences and Biotechnology, 2023)
Macronutrients are crucial for the growth, and development of plants due to their roles as structural components and redox-sensitive agents. Generally, the application of macronutrients leads to increased crop output, growth, and overall quality. While macronutrients play a role in every stage of a plant's life, scientists in fields such as plant physiology, biotechnology, and eco-physiology have recently focused on exploring additional aspects of these minerals, and their potential. Each macronutrient has a unique function in plant metabolism, and this study aims to examine the latest advancements in understanding the specific roles of macronutrients in plant growth and acclimatization. Furthermore, the study also discusses future research prospects in this field, highlighting the importance of ongoing investigations in maximizing plant productivity, and resilience.